The Development of the North-West Russia and the Delphi-method – evaluation of the industrial, social and logistical developments in the Murmansk Oblast - Yrjö Myllylä; Oleg Andreev (The Geographical Society of Northern Finland, 2005)
The development of the logistical system between the Murmansk Oblast area and other areas in the Barents Region assumes the anticipation of future commerce, industry and structure of population. The objective of the research is to create a scenario of the structure of commerce and industry and the population in the area and based on the this scenario to estimate the logistical development needs. In the research the strong prospective trends belonging to the scope of futures studies as well as the cluster approach will be used as theoretical starting points. The main method applied in the research is the Delphi-method, which belongs to the wider field of futures studies. The most important trends influencing the development of the Murmansk Oblast area are the main trend of logistical flows and the main trend of the technological development and globalisation based on the preliminary results from the Delphipanel's second round. By estimating the continuation of the trends until 2025, it can be stated that the main trend of globalisation would be strengthen in the first place then the main trend of the logistical flow and technological development which all would be strengthened or would have a slight increase. Among the individual trends with special emphasis most of them support clearly the development of transportation and logistical clusters, energy and environment clusters and the development of mining and refining of metals clusters. In the transportation and logistical clusters the development of railway connections and traffic forms the most important part, followed by the development of harbours and harbour services. According to the Murmansk panel the development of the energy cluster requires in the first place the construction of an oil pipe and then the development of electrical transfer capacity . The most important level of decision making concerning as well emphasised clusters as the most important logistical development undertakings related to them seems to be federal level which means the central ...